12 Years of Repair of Amalgam and Composite Resins: A Clinical Study - Estay, J.; Martin, J.; Viera, V.; Valdivieso, J.; Bersezio, C.; Vildosola, P.; Mjor, I. A.; Andrade, M. F. [UNESP]; Moraes, R. R.; Moncada, G.; Gordan, V. V.; Fernandez, E. (Operative Dentistry Inc, 2018)
Objective: The objective of this study was to clinically evaluate repaired posterior amalgam and composite restorations over a 12 year period, investigate the influence of repair in the survival of restorations, and compare their behavior with respect to controls. Methods: Thirty-four patients, 18 to 80 years of age with 167 restorations, 67 composite resin (RC), and 100 amalgam (AM) restorations, participated. Restorations with localized, marginal, anatomical deficiencies and/or secondary caries, and clinically judged suitable for repair or replacement according to US Public Health Service (USPHS) criteria, were randomly assigned to four groups: repair (n=35, 20 AM, 15 RC), replacement (n=43, 21 AM, 22 RC), positive control (n=71, 49 AM, 22 RC), or negative control (n=18, 10 AM, 8 RC). The quality of the restorations was blind scored according to the modified USPHS criteria. Two examiners scored them at initial status (kappa=0.74) and after one to five, 10, and 12 years (kappa=0.88). Wilcoxon and Mann-Whitney tests provided for comparisons within the same group and between years, respectively. Results: After 12 years, all groups behaved similarly in marginal adaptation, marginal stain, teeth sensitivity, anatomic form, and luster (p >= 0.05). Better behavior in roughness was observed in replaced RC (p=0.049). Conclusions: Given that most clinical parameters investigated were similar between all groups during the follow-up, the repair of RC and AM restorations is a good clinical option because it is minimally invasive and can consistently increase the longevity of restorations.